An investigation on the lubrication mechanism of MoS2 nano sheet in point contact: The manner of particle entering the contact area. (March 2017) - Wu, Hongxing; Qin, Liguo; Dong, Guangneng; Hua, Meng; Yang, Shuncheng; Zhang, Junfeng
Abstract: The goal of the work is to investigate the lubrication mechanism of MoS2 nano sheet. Polyisobutyleneamine Succinimide (PIBS) provides the steric repulsion to disperse nanoparticles in oil due to its long carbon chain. In the present study, the tribological behavior of nano-MoS2 sheet mixed with different percentages of PIBS was explored. The dispersed state and the mode of nano-MoS2 sheet entering the contact point were studied. Ball-on-disk results illustrated that the COF of nano-MoS2 in paraffin oil with free of PIBS was 26.2% compared with those containing 3 wt% PIBS, and the reduction of wear depth reached 41.9%. The nano-MoS2 sheets with 3 wt% PIBS were in discrete state in paraffin oil, which moved with side flow and could not enter the contact area to cause poor lubrication. Aggregation of particles took place in the case of low PIBS concentration and without PIBS, it entered the contact area and formed well-distributed MoS2 tribofilm to reduce friction and wear. Highlights: Friction of MoS2 without PIBS was reduced by 26.2% compared with that of 3% PIBS. Discrete MoS2 nano sheet moved with the side flow. Aggregated MoS2 nano sheet showed better lubrication performance. The lubrication mechanism of MoS2 nano sheet includes particle flow pattern effect.